2007
DOI: 10.1103/physrevlett.98.254101
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Signal Detection Using a Feed-Forward Oscillator Network

Abstract: We present the results of an experimental investigation of a network of nonlinear coupled oscillators which are coupled in feed-forward mode. By exploiting the nonlinear response of each oscillator near its intrinsic Hopf bifurcation point, we have found remarkable amplification of small signals over a narrow bandwidth with a large dynamic range. The effect is exploited to extract a small amplitude periodic signal from an input time series which is dominated by noise. Specifically, we have used this relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 25 publications
(22 reference statements)
0
20
0
Order By: Relevance
“…Chinese Sci Bull, 2011Bull, , 56: 3623-3629, doi: 10.1007 Systems that can detect and amplify signals at specific frequencies are commonplace in the natural world and most notably in the visual and auditory systems of animals [1]. Signal detection in animals is through light-and auralsensitive organs, constituted by a large number of networked units.…”
Section: Citationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chinese Sci Bull, 2011Bull, , 56: 3623-3629, doi: 10.1007 Systems that can detect and amplify signals at specific frequencies are commonplace in the natural world and most notably in the visual and auditory systems of animals [1]. Signal detection in animals is through light-and auralsensitive organs, constituted by a large number of networked units.…”
Section: Citationmentioning
confidence: 99%
“…Stoop et al suggested a van-der-Pol oscillator model to explain the active signal amplification in the Drosophila hearing system [4]. McCullen et al claimed that the generalized van-der-Pol oscillator with a 3-cell feed-forward network can explain the signal amplification well [1]. In detail, a double-well potential may be used to show how self-tuning works [10].…”
mentioning
confidence: 99%
“…The amplification and tuning properties of the human hair cells have been modelled by systems near a Hopf bifurcation . A Hopf bifurcation generates a small amplitude oscillation, in a nonlinear system, as a parameter is varied.…”
Section: Introductionmentioning
confidence: 99%
“…Cells behaving qualitatively similarly to the van der Pol oscillator have been used to obtain the amplification of the signal in some of these models . Stoop et al use a generalization of the van der Pol oscillator to model the antennal hearing organs of the fruit fly Drosophila melanogaster .…”
Section: Introductionmentioning
confidence: 99%
“…102 A potential application of this behavior is to the design of a nonlinear filter which selects oscillations close to a specific frequency and amplifies them. 58 Experimental proof-ofconcept can be found in McCullen et al 90 …”
Section: Anomalous Growth In Network Hopf Bifurcationmentioning
confidence: 99%